Personal and leadership competencies of hajj and umrah mentors: A quantitative and qualitative analysis - Rahman, Arif; Solahudin, Dindin; Herman, Herman; Alawiyah, Tuti; Ahmad, Zaidi bin (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - The main objective of this study is to understand how different aspects of Hajj and Umrah mentors' personal and leadership competencies influence pilgrims' experiences and the success of the mentoring process. Method- This research will make a significant contribution to the development of more effective and holistic Hajj and Umrah mentoring theory and practice. It combines objective and in-depth data analysis using a mixed methods design that combines the benefits of quantitative and qualitative approaches in a comprehensive study.The research participants consisted of 20 Hajj and Umrah mentors who were selected based on their experience, knowledge, or position relevant to the research topic. Information from the research participants was obtained through in-depth interviews and focus group discussions to explore their views, experiences and perceptions related to the research topic. Result - Based on quantitative and qualitative analysis of data obtained from research participants, it can be concluded that for personal competence consisting of five aspects where for the four categories the mentor is in the very high and high categories. while for leadership competence, 72.9% of Hajj and Umrah mentors are in the very high category, 20.4% are in the high category, and 6.7% are in the medium category. Implication - Overall, the combination of personal and leadership competencies is key in shaping effective mentors in the mentoring process. Originality/Value - Combine strong personal characteristics with the ability to lead by example and you will make a significant impact in guiding, supporting and inspiring your pilgrims to achieve their goals.